Evolução da irregularidade longitudinal em pavimentos flexíveis restaurados - Frandolozo, Glauber (2008)
The present work investigates the longitudinal irregularity evolution in restored flexible pavements in different situations of usage and coverings in highways that integrate the network under the concession of Univias consortium. The data analyzed are the results of periodical monitoring campaigns and are stored in the SGP (Pavements Management System) data base of the consortium, in the period of 2003 to 2005. Six sections were selected, measuring 5 kilometers each, in order to analyze the longitudinal irregularity evolution in a real-time scale. Subsequently, this evolution was interpreted in a comparative way with the irregularity decrease derived from the application of performance prediction models developed by Paterson and Queiroz. An investigation regarding the effects of different pavement restoration measures was also performed